More bits - more bucks? Measuring the impact of broadband internet on firm performance - Irene Bertschek; Daniel Cerquera; Gordon J. Klein (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2013)
The paper provides empirical evidence for the causal impact of broadband Internet on firms' labour productivity and realised process and product innovations. The analysis refers to the early phase of DSL expansion in Germany from 2001 to 2003, when roughly 60 percent of the German firms already used broadband Internet. Identification relies on instrumental variable estimation taking advantage of information on the availability of DSL broadband at the postal code level. The results show that broadband Internet has no impact on firms' labour productivity, whereas it exhibits a positive and significant impact on their innovation activity.
Keywords: D22; L23; O31; 330; labour productivity; product and process innovation; broadband Internet